To solve the quadratic equation \((x-1)(2x+5)=0\), we apply the Zero Product Property, which states that if the product of two factors equals zero, at least one of the factors must equal zero.
We can set each factor equal to zero:
- \(x - 1 = 0\)
- \(2x + 5 = 0\)
Now, solving each equation:
-
For \(x - 1 = 0\): \[ x = 1 \]
-
For \(2x + 5 = 0\): \[ 2x = -5 \implies x = -\frac{5}{2} \]
Thus, the values of \(x\) that make the equation \((x-1)(2x+5)=0\) equal to zero are:
\[ x = 1 \quad \text{and} \quad x = -\frac{5}{2} \]
Therefore, the correct response is:
The quadratic equation will equal zero when \(x = -\frac{5}{2}\) and \(x = 1\).